2023
DOI: 10.1186/s12879-023-08706-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between gut microbiota and influenza: a bidirectional two-sample mendelian randomization study

Fan Xu,
Xiuyuan Gan,
Yang Tao
et al.

Abstract: Background Previous observational studies have indicated a correlation between the gut microbiota and influenza; however, the exact nature of the bidirectional causal connection remains uncertain. Method A two-way, two-sample Mendelian randomization (MR) study was conducted to evaluate the possible causal connection between the gut microbiota and the two outcomes of influenza (pneumonia without influenza and influenza pneumonia). The statistical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…The bacterial strains present in the bacterial formulation enhanced the production of both nuclear factor erythroid 2p45-related factor 2 and its target Heme oxygenase-1, exerting antiviral effects through the reduction of oxidative stress [ 72 ]. Interestingly, Xu et al reported that the genus Streptococcus was negatively associated with influenza outcomes in FinnGen cohorts, consistent with our findings in the Chinese population [ 22 ]. However, we also found that Streptococcus mitis was positively associated with H7N9 susceptibility.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The bacterial strains present in the bacterial formulation enhanced the production of both nuclear factor erythroid 2p45-related factor 2 and its target Heme oxygenase-1, exerting antiviral effects through the reduction of oxidative stress [ 72 ]. Interestingly, Xu et al reported that the genus Streptococcus was negatively associated with influenza outcomes in FinnGen cohorts, consistent with our findings in the Chinese population [ 22 ]. However, we also found that Streptococcus mitis was positively associated with H7N9 susceptibility.…”
Section: Discussionsupporting
confidence: 92%
“…Xu et al employed MR to investigate the causal effect of gut microbiota on seasonal influenza and influenza-induced pneumonia in Finland. In their study, the identification of intestinal flora was limited to the genus level [ 22 ]. In this study, we performed a systematic two-sample MR study to explore the causal effect of species-level gut microbiota on avian IAV H7N9 susceptibility and H1N1pdm09 severity in Chinese.…”
Section: Introductionmentioning
confidence: 99%